The Impact of Pressurization on Anode-Supported and Electrolyte-Supported Planar Solid Oxide Fuel Cells at 750oC 850oC. (2nd June 2015) - Shy, Shenqyang Steven; Hsieh, Y.D.; Liang, Jyun-De
Abstract : The impact of pressurization on anode and electrolyte-supported cells (ASC/ESC) is measured in a high-pressure SOFC test facility using the same single-cell stack setup, a planar fuel cell with rib-channel flow distributors, under the same experimental conditions (i.e. same flow rate, temperature, pressure). Results show that at T = 850°C and 0.7 V, power densities of ASC/ESC increase from 309/193 mW cm -2 to 476/250 mW cm -2, as p increases from 1 atm to 5 atm. As T increases from 750°C to 850°C at 0.7 V, power densities of ASC/ESC increase from 175/97 mW cm -2 to 309/193mW cm -2 at p = 1 atm, while at p = 5 atm, the corresponding increases of power densities are 281/137 mW cm -2 to 476/250 mWcm -2 . It is found that ASC is more sensitive to pressurization than ESC, while the latter is more temperature-sensitive. Corresponding electrochemical impedance spectra explain these results.